Moral Hazard Problem in Public Policy Makers - Alam, Noor (European Scientific Journal, ESJ, 2022)
The moral hazard problem in government organizations is very recurrent due to weak compensation system (i.e., take-home salary) and non-existence of any additional premium (e.g., ownership of stocks) for public policy makers as compared to their counterpart in private firms, hence it weakens their proprietorship of their organization. Since there is a principal-agent relationship between citizens and public policy makers, therefore, a loss in public goods and services to citizens signals meaningful level of moral hazard problem in public policy makers being the agents. The menace of moral hazard problem can be, lessened through a proper Reward Punishment Approach (RPA). Under existing setup, a weak compensation system with severe punishment mechanics indicates flaws in PRA which needs improvement through reforms in its existing structure. This paper recommends, to bring the compensation system (i.e., take home salary in terms of cash & a provision of additional premium) at par with market-based package along with various perquisites. The study expects a bare minimum financial implication which may be affordable for the government and decrease in moral hazard problem at least to some extent, leading to a better delivery of public goods and services for the citizens of the country.